Tangible nanocomposites with diverse properties for heart valve application - Vellayappan, Muthu Vignesh (2015)
Cardiovascular disease claims millions of lives every year throughout the world. Biomaterials are used widely for the treatment of this fatal disease. With the advent of nanotechnology, the use of nanocomposites has become almost inevitable in the field of biomaterials. The versatile properties of nanocomposites, such as improved durability and biocompatibility, make them an ideal choice for various biomedical applications. Among the various nanocomposites, polyhedral oligomeric silsesquioxane-poly(carbonate-urea)urethane, bacterial cellulose with polyvinyl alcohol, carbon nanotubes, graphene oxide and nano-hydroxyapatite nanocomposites have gained popularity as putative choices for biomaterials in cardiovascular applications owing to their superior properties. In this review, various studies performed utilizing these nanocomposites for improving the mechanical strength, anti-calcification potential and hemocompatibility of heart valves are reviewed and summarized. The primary motive of this work is to shed light on the emerging nanocomposites for heart valve applications. Furthermore, we aim to promote the prospects of these nanocomposites in the campaign against cardiovascular diseases.